PEMBERDAYAAN GURU BAHASA SUNDA MELALUI PELATIHAN PENULISAN ILMIAH POPULER BERBASIS LITERASI BUDAYA DAN EDUKASI LINGKUNGAN - Nugraha, Haris Santosa; Alia, Dwi; Cahyani, Isah; Hendrayana, Dian; Kusdinar, Hidayat; Herdiyanti, Febri; Dakir, Siti Humaira Ramadhani (Universitas Padjadjaran, 2026)
This community engagement program was implemented to enhance the capacity of Sundanese language teachers in writing popular scientific articles grounded in cultural literacy and environmental education. The main challenges faced by the partner were the teachers’ limited writing skills and the lack of accessible publication platforms that promote local culture and ecological awareness. The program was conducted through a combination of online and offline sessions at SMAN 1 Cisarua, involving twenty teachers as participants. The objective of the program was to develop teachers’ ability to write contextual, communicative, and inspiring articles that document cultural values and environmental issues within their local surroundings. The implementation consisted of several stages, including orientation, training in popular scientific writing, the application of digital technology in the creative process, intensive mentoring, and program sustainability. Participants were actively engaged through practical writing activities based on field observations and personal reflections on cultural and environmental phenomena around their schools. The results indicated a significant improvement in participants’ writing competence, particularly in terms of topic relevance, data enrichment, narrative structure, and the strength of the cultural messages conveyed. Fifteen articles were successfully produced and prepared for submission to both print and digital media. Furthermore, the program fostered participants’ awareness of the importance of digital technology as a tool for the exploration, documentation, and dissemination of local knowledge. Overall, this initiative contributed to enhancing teacher professionalism and supporting the preservation of Sundanese cultural heritage through meaningful and inspiring popular scientific writing.Kegiatan pengabdian kepada masyarakat ini dilaksanakan untuk meningkatkan kapasitas guru Bahasa Sunda dalam menulis karya ilmiah populer berbasis literasi budaya dan edukasi lingkungan. Permasalahan utama mitra adalah rendahnya keterampilan menulis populer dan minimnya akses terhadap media publikasi yang mengangkat nilai budaya lokal dan kepedulian terhadap lingkungan. Program dilaksanakan secara kombinasi daring dan luring di SMAN 1 Cisarua dengan melibatkan dua puluh guru sebagai peserta. Tujuan kegiatan ini adalah membekali peserta dengan kemampuan menulis secara komunikatif, kontekstual, dan inspiratif, sehingga mampu menghadirkan isu budaya dan lingkungan dalam bentuk karya ilmiah populer yang layak disebarluaskan kepada masyarakat. Pelaksanaan kegiatan dilakukan melalui beberapa tahap, yaitu sosialisasi, pelatihan penulisan ilmiah populer, penerapan teknologi digital dalam proses kreatif, pendampingan intensif, dan keberlanjutan program. Peserta dilibatkan secara aktif melalui praktik menulis berbasis pengalaman lapangan dan refleksi personal terhadap fenomena budaya dan lingkungan di sekitar sekolah. Hasil kegiatan menunjukkan peningkatan signifikan dalam kemampuan menulis peserta, terutama pada aspek ketepatan pemilihan tema, kelengkapan data lapangan, struktur naratif, dan kekuatan pesan budaya yang disampaikan. Sebanyak lima belas artikel berhasil disusun dan difasilitasi untuk dipublikasikan melalui media cetak dan digital. Selain peningkatan keterampilan menulis, peserta menunjukkan perubahan sikap dan kesadaran baru terhadap pemanfaatan teknologi digital sebagai alat eksplorasi, dokumentasi, dan penyebaran pengetahuan lokal. Program ini berkontribusi nyata dalam penguatan profesionalisme guru serta pelestarian kearifan lokal melalui karya ilmiah populer yang inspiratif dan edukatif.